Late Complications Following Continuous-Flow, Left Ventricular Assist Device Implantation - Joshua C Grimm; Jonathan T Magruder; Clinton D Kemp; Ashish S Shah (Frontiers in Surgery, 2015)
Left ventricular assist devices have become standard therapy for patients with end stage heart failure. They represent potential long term solutions for a growing public health problem. However, initial enthusiasm for this technology has been tempered by challenges posed by long term support. This review examines these challenges and out current understanding of their etiologies.